DEVELOPING WRITING MATERIALS FOR DEAF STUDENTS - Hamdan Anwari (EduLite: Journal of English Education, Literature and Culture, 2017)
This research is aimed at finding out the suitable writing material for deaf students. This research belongs to research and development. The participants of this research were the eleventh graders of SLB Muhammadiyah Dekso Kalibawang of semester 1 in academic year 2013/2014 which consisted of two students. The instruments used in collecting data were questionnaires. The questionnaires were used in the need analysis, material evaluation and students’ response. The data were analyzed descriptively by using percentage. Based on the need analysis, it was found out that students’ need is suitable with material for writing. In developing  syllabus, existing syllabus must be added with some exercises. In developing material is in the form of hand out. The hand out is writing material for the deaf students. The developed material is for the first semester academic year of 2013/2014. It consists of  three  units, five topics and nineteen activities. In the material evaluation from two experts, the developed materials facilitate the deaf students to write. Based on the student’s response, the developed material is appropriate with their English level competence.